The novel chicken interleukin 26 protein is overexpressed in T cells and induces proinflammatory cytokines. (December 2016) - Truong, Anh; Park, Boyeong; Ban, Jihye; Hong, Yeong
Abstract In the present study, we describe the cloning and functional characterization of chicken interleukin 26 (ChIL-26). ChIL-26, a member of the IL-10 cytokine family, induces the production of proinflammatory cytokines by T cells. The ChIL-26 cDNA encodes an 82-amino-acid protein whose amino acid sequence has 22.63, 46.31 and 43.15% homology with human IL-26, pig IL-26 and canary IL-26, respectively. ChIL-26 signals through a heterodimeric receptor complex composed of the IL-20R1 and IL-10R2 chains, which are expressed primarily in the CU91 T cell line as well as CD4+ and CD8+ T cells. Recombinant ChIL-26 protein induced Th1 cytokines (IL-16 and IFN-γ), Th2 cytokines (IL-4, IL-6 and IL-10), Th17 cytokines (IL-17A, IL-17D, and IL-17F), and chemokine transcripts (mainly CCL3, CCL4, CCL5, CCL20 and CXCL13) in the CU91 T cell line and in CD4+ and CD8+ T cells, however IL-18 was not expressed in the CU91 T cell line. Taken together, the data demonstrates that T cells express the functional ChIL-26 receptor complex and that ChIL-26 modulates T cell proliferation and proinflammatory gene expression. To the best of our knowledge, this is the first report of cloned ChIL-26. We evaluated its functional roles, particularly in the pathogenic costimulation of T cells, which may be significantly associated with the induction of cytokines.